Congenital flat vascular anomalies: differential diagnosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2020)
This is a retrospective study of 81 cases of congenital flat vascular anomalies of the skin – salmon patch, port-wine stain, minimal growth hemangioma, capillary malformation / arteriovenous malformation syndrome and cutis marmorata telangiectatica congenita – consecutively examined from January, 1 to December, 31 2019. Clinical and dermoscopic data of these patients were examined in order to identify their role in the differential diagnosis, which is not always easy. Clinical data are most useful but not always sufficient; dermoscopic data are useful but not diriment; in doubtful cases the clinical observation for a few days is essential to establish the correct diagnosis. The latter is necessary in these anomalies that have a very different prognosis and therapy.